Dosimetric Comparison Between Jaw Tracking and No Jaw Tracking in Intensity-Modulated Radiation Therapy. (19th July 2019) - Yao, Shengyu; Zhang, Yin; Chen, Tingfeng; Zhao, Guoqi; Hu, Zhekai; Lu, Xiaokai; Liu, Yong
Purpose: This article compares the dosimetric differences between jaw tracking and no jaw tracking technique in static intensity-modulated radiation therapy plans of large and small tumors. Methods: Eight plans with large tumor (nasopharyngeal carcinoma, volume range: 510.9 to 768.0 cm 3 ) and 8 plans with small tumor (single brain metastasis, volume range: 5.3 to 9.9 cm 3 ) treated with jaw tracking on Varian EDGE LINAC were chosen and recalculated with no jaw tracking to study the dosimetric differences. We compared the differences of organ-at-risk doses (Dmax, Dmean), monitor units, and γ passing rate of plan verification (3mm/3%, threshold 10%; 2mm/2%, threshold 10%) between the 2 techniques. Results: The organ-at-risk doses of nasopharyngeal carcinoma cases having jaw tracking are all less than those with no jaw tracking. The Dmax and Dmean of organ-at-risks reduced 0.61% to 17.65% and 2.17% to 19.32%, P < .05, respectively. In cases with single brain metastasis, the organ-at-risk doses with jaw tracking were also lower than no jaw tracking. The Dmax and Dmean of organ-at-risk doses reduced 0.84% to 1.52% and 0.90% to 1.86%, P < .05, respectively. The monitor units for the large tumor and small tumor were increased by 2.41% and 1.1%, respectively. The γ passing rates (3mm/3%, th10%; 2mm/2%, th10%) of nasopharyngeal carcinoma plans are 99.89% ± 0.06% (jaw tracking) versus 99.56% ± 0.19% (no jaw tracking; P = .127); 97.15% ± 0.98% (jaw tracking) versus 91.90% ± 1.40% (no jaw tracking; P = .000), and the γ passing rates (3mm/3%, th10%; 2mm/2%, th10%) of brain metastasis plans are 99.97% ± 0.05% (jaw tracking) versus 99.44% ± 1.24% (no jaw tracking; P = .251), 98.65% ± 1.27% (jaw tracking) versus 93.35% ± 2.72% (no jaw tracking; P = .000). Conclusion: Jaw tracking can reduce the dose of organ-at-risks compared to no jaw tracking, and the effect is more significant for plans with large tumor. The γ passing rate of plans with jaw tracking is also higher than the plans with no jaw tracking. Although the monitor units in plans of jaw tracking will increase slightly, it is recommended to use jaw tracking in static intensity-modulated radiation therapy both in large and in small tumors.